Primerjalna študija postopkov sušenja hmelja (Humulus lupulus L.) - Košir, Iztok Jože (Hmeljarski bilten, 2025)
The post-harvest drying (kilning) of hops is a critical process step in hop production, influencing moisture content, chemical composition (alpha-acids, essential oils), storage stability and ultimately beer quality. This paper compares the typical drying procedures employed in Slovenia and the United States, with an emphasis on process solutions and integration into packaging/storage together with quality considerations. The comparison highlights how smaller hop growers in Slovenia emphasise gentle drying for aroma preservation, while large-scale U.S. operations beside that emphasise throughput, consistency and integration with pelletising and cold-chain logistics. Based on literature and industry practice, the paper offers recommendations for optimal drying protocols and points that could be improved.
Keywords: hmelj; hops; kakovost; kilning; product quality; Slovenia; Slovenija; sušenje; United States of America; Združene države Amerike